IMPLEMENTASI DAN INISIASI PELEMBAGAAN MANAJEMEN BERBASIS SEKOLAH (MBS) PADA LEMBAGA PENDIDIKAN TENAGA KEPENDIDIKAN (LPTK) - Patta Bundu (Al Qalam, 2010)
This research aims at studying the implementation of School Based Management (SBM) that has been implemented both in the Elementary Schools and Junior High Schools, and proposing a model on how School Based Management is institutionalized at a university. The implementation will be focused on three pillars of SBM: school management, effective teaching, and community participation. The result of the research shows that the implementation of SBM at Elementary schools and Junior High Schools still need serious improvement. The understanding on School Based Management based on its three pillars at university (LPTK) is various and still needs socialization to the leaders and lectures. The initial phase is arranged thourgh five steps: socialization, training, workshop, internship, and mentoring, Supporting products of the SBM implementation that have become a guidance book and a reference book may be modified. Keywords: MBS, Effective teaching, LPTK.